Pemusik Jalanan Studi Deskriptif Pemusik Jalanan Di Daerah Pulai Lubuk Minturun Kota Padang - Wirvan Andika; Esy Maestro (SENDRATASIK UNP, 2021)
This research aims to find and describe Rian's activities as one of the street musicians in Padang City. This type of research is Qualitative Research. The main instruments in the study were researchers themselves and assisted with supporting instruments such as stationery, recording devices and cameras. Data collection techniques are carried out by observation, interview, library study and documentation. The steps to analyze the data are to collect data and describe the data and draw conclusions. The results showed that there are still many lay people who think street musicians or worshippers are interfering with comfort and even being indifferent to them. Street musicians or performers are a profession run by art actors or art workers who display and sell their talents to the public. They're not beggars or anything like that. They are the perpetrators of art who are on the streets, they are arguably disadvantaged because of weak economic factors and forcing them to express themselves on the streets. They should get better treatment and apresization from society in general, because there are still many people who have talent and are very much worthy of our appreciation, because with the appreciation that we give can support their lives